THE REDUCTION IN LOSS OF THE AIRCRAFT INDUSTRY BY RESTRUCTURING PRODUCTION ASSETS - V. P. Panagushin; O. M. Sevryukov; N. K. Chayka; V. Yu. Chayka (Стратегические решения и риск-менеджмент)
Ways of restructuring the company's assets are anakysed. Analysis of reasons of loss-making enterprises is made. A set of measures for loading of productive areas is proposed to address the causes of the loss.Restructuring of productive assets based on the connection of the plant and an industrial park us consideredto reduce losses of enterprises.